A Unique Way to Generate Password at Random Basis and Sending it Using a New Steganography Technique - Sabyasachi Pramanik; R. P Singh; Ramkrishna Ghosh; Samir K. Bandyopadhyay (IAES Indonesian Section, 2020)
Data hiding is a technique for secure transmission of confidential data. Many data hiding techniques exist and steganography is the most important one. This paper presents a new steganography method in spatial domain. We use steganography to send confidential information from sender to receiver. Here, we generate password at random basis in a unique way based on system time and date. Then we send this confidential password using steganography by implementing a totally new embedding and extraction technique based on exact length of bits in binary representation of ASCII values. Here, confidential text information is embedded into cover image generating a stego image and sent to receiver maintaining top level secrecy.